Women, gender, and terrorism - Sjoberg, Laura, 1979-; Gentry, Caron E. (Studies in security and international affairs., 2011)
In the last decade the world has witnessed a rise in women's participation in terrorism. Women, Gender, and Terrorism explores women's relationship with terrorism, with a keen eye on the political, gender, racial, and cultural dynamics of the contemporary world. Throughout most of the twentieth century, it was rare to hear about women terrorists. In the new millennium, however, women have increasƯingly taken active roles in carrying out suicide bombings, hijacking airƯplanes, and taking hostages in such places as Palestine, Iraq, Afghanistan, Sri Lanka, Lebanon, and Chechnya. These women terrorists have been the subject of a substantial amount of media and scholarly attention, but the analysis of women, gender, and terrorism has been sparse and riddled with stereotypical thinking about women's capabilities and motivations. In the first section of this volume, contributors offer an overview of women's participation in and relationships with contemporary terrorism, and a historical chapter traces their involvement in the politics and conflicts of Islamic societies. The next section includes empirical and theoretical analysis of terrorist movements in Chechnya, Kashmir, Palestine, and Sri Lanka. The third section turns to women's involvement in al Qaeda and includes critical interrogations of the gendered media and the scholarly presentations of those women. The conclusion offers ways to further explore the subject of gender and terrorism based on the contributions made to the volume. Contributors to Women, Gender, and Terrorism expand our understanding of terrorism, one of the most troubling and complicated facets of the modern world.